1996
DOI: 10.1161/01.hyp.27.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Situ Measurement of Nitric Oxide in Mesenteric Resistance Arteries

Abstract: The endothelium plays a critical role in maintaining vascular tone by releasing vasoconstrictor and vasodilator substances. Endothelium-derived nitric oxide is a vasodilator that can be rapidly inactivated by superoxide (reaction rate constant, K = 3.6 x 10(9) L/mol per second). The measurement of nitric oxide concentration in biological systems is a challenging analytic problem because nitric oxide is also rapidly inactivated by Fe(II), Fe(III), and O2, all of which are found in great abundance in biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(164 citation statements)
references
References 10 publications
12
147
1
4
Order By: Relevance
“…For example, hypertension is associated with increased inhibition of NO signaling by superoxide, whereas NO release remains unaffected. 17 Bauersachs et al 18 also reported that endothelial dysfunction in ischemic heart failure was induced by an increase in vascular superoxide production despite enhanced vascular endothelial nitric oxide synthase (eNOS) and soluble guanylate cyclase expression. Importantly, eNOS is a cytochrome P450 reductase-like enzyme that produces superoxide under certain pathological conditions.…”
Section: Fukuo Et Al Nifedipine Indirectly Upregulates Endothelial Sodmentioning
confidence: 99%
“…For example, hypertension is associated with increased inhibition of NO signaling by superoxide, whereas NO release remains unaffected. 17 Bauersachs et al 18 also reported that endothelial dysfunction in ischemic heart failure was induced by an increase in vascular superoxide production despite enhanced vascular endothelial nitric oxide synthase (eNOS) and soluble guanylate cyclase expression. Importantly, eNOS is a cytochrome P450 reductase-like enzyme that produces superoxide under certain pathological conditions.…”
Section: Fukuo Et Al Nifedipine Indirectly Upregulates Endothelial Sodmentioning
confidence: 99%
“…Other authors (Nava & Luscher 1995) have showed that, at least in the SHR, vascular nitric oxide production is augmented, but some overproduction of nitric oxide scavengers from the superoxide dismutase pathway break down the nitric oxide leading to endothelial dysfunction (Tschudi et al 1996). We have demonstrated that aortas from SHR-UNX do not show myogenic tone as a consequence of the nitric oxide released on the basal tone.…”
Section: Sodiummentioning
confidence: 58%
“…Estudios llevados a cabo en pacientes hipertensos, han mostrado que presenta una alteración de la respuesta vasodilatadora a los estimulantes del NO, pudiendo deberse a una reducción en su síntesis [26][27][28] , sin estar relacionado en exclusiva a una menor disponibilidad de sustrato 29 , debido a una mayor descomposición del NO por superóxido 30 o por la inhibición por sustancias ciclooxigenasa dependientes 31 .…”
Section: Efectos De Hipertensión Y Obesidad En La Función Del Endoteliounclassified